THE CONCEPT OF “TESTATE SUCCESSION” IN THE ROMANIAN AND GEORGIAN LEGAL SYSTEMS (TERMINOLOGICAL SIMILARITIES AND DIFFERENCES) - IRINA GVELESIANI (Challenges of the Knowledge Society, 2013)
The death of an individual never causes an automatic termination of his (her) rights and obligations. They are transferred to his (her) descendants. The permanent connection of generations has inspired the world civilizations to create rules of succession for establishing people’s obedience to them. In the old times, the transmission of property of the Romanian people was governed by the legislation, which had been created under the influence of the Roman law. According to the conception of this legislation, a deceased person’s property had to stay with his blood relatives i.e. within the same family. On the background of these circumstances, a surviving spouse suffered disadvantages. A widow’s rights were limited in accordance with the old Georgian legislation too – the hereditary property was mainly divided between the male issue, while females owned only wedding gifts (dowry). However, the area of family law has suffered crucial changes throughout the centuries. Nowadays, during the times of globalization, these changes are directed towards the internationalization of legal systems of the world. Juridical differences are becoming irrelevant and females’ rights are equalized with the males’ ones. The given paper is dedicated to the precise study of the Romanian and Georgian “testate successions”. It singles out major terminological units and discusses women’s rights vis-à-vis men’s ones.